Bad Credit Problems in Financing Institutions In Makassar City - Nawi, Syahruddin; Wahab, Mirnawati; Arief, Muh. (Jurnal Ilmiah Global Education, 2024)
This study focuses on the study of the Problem of Bad Loans of Financial Institutions in various agreements and the factors that affect the creation of bad loans in various agreements in Makassar City, South Sulawesi Province. The type of research is empirical legal research (nondoctrinal), which is research that observes social phenomena in society, in this case the problem of bad loans of financial institutions in various agreements. In addition, it also examines the factors that affect the occurrence of bad loans at financing institutions in various agreements in Makassar City, South Sulawesi Province. The influencing factors are, standard contract (regulation) factors, provit, legal awareness, business failure and the Covid 19 factor. The results of the study concluded that 1). The frequency or quantity of bad loans at financial institutions in Makassar City is quite high. 2). Factors that affect the occurrence of bad loans at financial institutions in Makassar City are standard contract (regulation) factors, provit, legal awareness, business failure and the Covid 19 factor.